ANALYSIS AND DESIGN OF SCM METHODS IN TOKO 66 WEBSITE-BASED - Maha Putra, Guntur; Prasasti, Andrean; Dwi Sena, Maulana (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Clothing is a basic human need besides food and shelter. Human needs clothing to protect and cover them self. Toko 66 is a business that operates in the field of products and services. This business offers various types of products such as clothes, trousers and also shirts that are second hand, aka used. The absence of distribution transaction channels from upstream to downstream is one of the business problems at Toko 66. Therefore, a system such as Supply Chain Management is needed which can manage the flow of transactions from upstream to downstream and can also make it easier for owners to create sales reports. Based on the research results, it can be found that a system has been created that implements web-based Supply Chain Management to help owners, admins, suppliers and customers in carrying out transaction flows from upstream to downstream. The business process from upstream to downstream has also been running in accordance with the Supply Chain Management procedures that apply at the research object location so that it can provide information regarding the existence of sufficient product stock to ensure a good transaction flow from upstream to downstream.            Keywords: supply chain management; clothes; stock; transaction; distribution